2019
DOI: 10.1021/acsmaterialslett.9b00412
|View full text |Cite
|
Sign up to set email alerts
|

Direct Quantification of Cu Vacancies and Spatial Localization of Surface Plasmon Resonances in Copper Phosphide Nanocrystals

Abstract: Copper chalcogenides and pnictogenides often behave as heavily doped p-type semiconductors due to the presence of a high density of Cu vacancies, with corresponding hole carriers in the valence band. If the free carrier concentration is high enough, localized surface plasmon resonances can be sustained in nanocrystals of these materials, with frequencies that are typically observed in the infra-red region of the spectrum (<1 eV), differently from the typical resonances featured in the visible range by metallic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
(81 reference statements)
4
11
0
Order By: Relevance
“…For instance, cation Pb vacancies are expected to determine intrinsic pdoping. 37 A DFT-calculated density of states shows that this picture holds for cation neutral vacancies (V Pb0 , V Cs0 ), while the opposite behavior (i.e. n-doping) is observed in the case of anion neutral vacancies (V Br0 ), in agreement with the low (high) electronegativity of Pb and Cs (Br) atoms.…”
Section: Stem Imagingmentioning
confidence: 72%
“…For instance, cation Pb vacancies are expected to determine intrinsic pdoping. 37 A DFT-calculated density of states shows that this picture holds for cation neutral vacancies (V Pb0 , V Cs0 ), while the opposite behavior (i.e. n-doping) is observed in the case of anion neutral vacancies (V Br0 ), in agreement with the low (high) electronegativity of Pb and Cs (Br) atoms.…”
Section: Stem Imagingmentioning
confidence: 72%
“…32,33 It was recently demonstrated that copper vacancies in copper phosphide (Cu 3−x P) nanocrystals also generate excess delocalized holes and near-IR LSPR absorption. 34,35 In contrast to the copper chalcogenides, which often undergo phase transformations with dynamic redox tuning, 36 Cu 3−x P exists as the sole copper-rich phase. This phase-stability and potential for distinct surface chemistry make Cu 3−x P a unique system for colloidal semiconductor nanoplasmonics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Colloidal semiconductor nanocrystals capable of supporting excess delocalized charge carriers are an important class of emerging electronic materials because of the potential for hosting tunable carrier densities. Carrier concentrations can often be modulated via defect incorporation and activation during synthesis ,− or via post-synthetic redox or photoredox manipulations. ,, These techniques allow for access to tunable photophysical properties in semiconductor nanocrystals, including localized surface plasmon resonances (LSPRs) in the mid- or near-IR. ,− , Nanocrystals in which the LSPR absorption is derived from delocalized holes , are relatively uncommon, with copper chalcogenides (CuE or Cu 2– x E; E = S, Se, and Te) being the most widely studied. ,,,,, In these materials, delocalized holes arise to compensate for copper vacancies, resulting in degenerately doped semiconductors with LSPR absorption in the near-IR that has been exploited for surface-enhanced Raman scattering, plasmon-enhanced chemical conversion, and ultrafast optical switching. , It was recently demonstrated that copper vacancies in copper phosphide (Cu 3– x P) nanocrystals also generate excess delocalized holes and near-IR LSPR absorption. , In contrast to the copper chalcogenides, which often undergo phase transformations with dynamic redox tuning, Cu 3– x P exists as the sole copper-rich phase. This phase-stability and potential for distinct surface chemistry make Cu 3– x P a unique system for colloidal semiconductor nanoplasmonics.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to study dopant distribution in semiconductors, the segregation of tin in the surface of indium tin oxide has shown an influence on dopant activation in the matrix [10]. The role of rich Cu vacancies and hence valance band holes on SPR in CuP nanocrystals studied on the basis of scanning transmission electron microscopy measurements has been reported [11]. NMR spectroscopy of copper solenoid with different Cu compositions exhibited plasmonic characteristics in a low doped regime that depends on the charge density of the carriers [12].…”
Section: Introductionmentioning
confidence: 99%